2011
DOI: 10.1590/s0100-40422011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality comparison between rural farms and riparian wells in the western Amazon, Brazil

Abstract: Recebido em 28/10/09; aceito em 30/7/10; publicado na web em 17/11/10Groundwater quality of a riparian forest is compared to wells in surrounding rural areas at Urupá River basin. Groundwater types were calcium bicarbonated at left margin and sodium chloride at right, whereas riparian wells exhibited a combination of both (sodium bicarbonate). Groundwater was mostly solute-depleted with concentrations within permissible limits for human consumption, except for nitrate. Isotopic composition suggests that inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
2
0
3
Order By: Relevance
“…These values are in the range of the observations made in previous works (0.04-2.8 mgN-NO3.L -1 ; McClain et al, 1994;Leite et al, 2011). Concerning the Garonne basin, the SWAT model simulated average nitrate concentrations of 8.6 ± 5.8 mgN-NO3.L -1 in aquifers while past research measured concentrations between 3.86 and 17.95 mgN-NO3.L -1 (Jégo et al, 2012;Sun et al, 2018).…”
Section: Temporal and Spatial Validity Of The Resulting Floodplains Denitrification Ratessupporting
confidence: 77%
“…These values are in the range of the observations made in previous works (0.04-2.8 mgN-NO3.L -1 ; McClain et al, 1994;Leite et al, 2011). Concerning the Garonne basin, the SWAT model simulated average nitrate concentrations of 8.6 ± 5.8 mgN-NO3.L -1 in aquifers while past research measured concentrations between 3.86 and 17.95 mgN-NO3.L -1 (Jégo et al, 2012;Sun et al, 2018).…”
Section: Temporal and Spatial Validity Of The Resulting Floodplains Denitrification Ratessupporting
confidence: 77%
“…A faixa de valores apresentados expressa ser de baixa salinidade a água dos poços, conforme define o autor citado. Leite et al (2010) explica que os ecossistemas florestais da região amazônica, pouco antropizados, apresentam baixos valores de condutividade e reforça que valores mais elevados de condutividade estão associados a áreas onde predominam atividades agrícolas, semelhante a área estudada em que os maiores valores de CE foram observados nos poços próximo à horta. Os valores de nitrato (NO 3 -) nos pontos estudados variaram entre 3,4 a 15,1, com média de 9,36 mg/L, ao período chuvoso.…”
Section: Qualidade Da áGua Subterrâneaunclassified
“…Analyzing data of 10 small watersheds throughout the Amazon, Neill et al [29] concluded that the contribution of overland flow as a source of stream flow was greater in pasture watersheds than in forest watersheds of comparable size. Large pasture areas, with narrow or nonexistent riparian forests, can alter the chemical composition of rivers, particularly for streamwater cation concentrations and alkalinity [30,31]. As a result of increased root and microbial respiration during the wet season, generated CO 2 in soils drives cation-bicarbonate leaching from the landscape to streams and stream water.…”
Section: Watershed Biogeochemistry Affected By Large Crops and Pasturementioning
confidence: 99%
“…As a result of increased root and microbial respiration during the wet season, generated CO 2 in soils drives cation-bicarbonate leaching from the landscape to streams and stream water. It is assumed that cations (derived from ashes of forest burning for pasture conversion) and bicarbonates are mainly flushed from surface soil layers by rainfall rather than as the products of deep soil weathering carried by groundwater, with cation concentrations increasing during larger discharge periods [30,31].…”
Section: Watershed Biogeochemistry Affected By Large Crops and Pasturementioning
confidence: 99%